Between earth and sky - Skenandore, Amanda (Kensington Books, 2018)
"On a quiet Philadelphia morning in 1906, a newspaper headline catapults Alma Mitchell back to her past. A federal agent is dead, and the murder suspect is Almas childhood friend, Harry Muskrat. Harry--or Asku, as Alma knew him--was the most promising student at the 'savage-taming' boarding school run by her father, where Alma was the only white pupil. Created in the wake of the Indian Wars, the Stover School was intended to assimilate the children of neighboring reservations. Instead, it robbed them of everything they'd known--language, customs, even their names--and left a heartbreaking legacy in its wake...she barely recognizes the man Asku has become, cold and embittered at being an outcast in the white world and a ghost in his own. Her lawyer husband, Stewart, reluctantly agrees to help defend Asku for Alma's sake. To do so, Alma must revisit the painful secrets she has kept hidden from everyone--especially Stewart"--Amazon.com.